Student Opinions on Mobile Augmented Reality Application and Developed Content in Science Class - Karagozlu, Damla; Özdamlı, Fezile (TEM Journal, 2017)
As one of the most important branches of science, natural science studies have never lost their currency. The purpose of this study is to examine the development process of Augmented Reality contents which were developed using a design-based research method with the purpose of using it in teaching of natural science topics and to look into student evaluations. In the study which employed design-based research model, developed contents were applied, analysed and re-designed with students constantly. The study group of the research consisted of forty 7th grade students at a private college in 2016-2017 fall semester. Augmented reality contents developed for science teaching were evaluated by teachers and students as effective. According to the teacher and student opinions, it was concluded that augmented reality contents of science teaching developed during design-based research process was nice, easily applicable and useful. It can be said that while developing educative materials for students, applying design-based research model and paying attention to material design principles secures the effectiveness of the developed material.